Explaining a Pattern for Applying Environmental Accounting - Sadrara, Mehrdad; Kari, MohammadJavad Tasaddi; Dalivand, Mojtaba Bahari (Journal of Environmental Accounting and Management, 2026)
Considering the importance of the environment in maintaining and continuing the survival of living organisms, the aim of the current research is to provide a model for applying environmental accounting (EA). The current research is of a qualitative type, the data of which was obtained through in-depth semi-structured interviews with 11 financial managers of the reporting units in 2023, and this process continued until theoretical saturation was reached. The method of selecting the respondents is based on the snowball sampling method and the data analysis process is based on the Grounded-Theory. The research findings indicate that the implementation of EA is influenced by two main categories and five subcategories of causal factors, three main categories and seven subcategories of contextual factors, two main categories and seven subcategories of intervening factors, two main categories and five subcategories of strategies, and three main categories and six subcategories of outcomes. Based on the research findings, focusing on the necessary infrastructure and securing governmental and social support can pave the way for the implementation of EA. Additionally, organizational culture and structure, technology and information systems, as well as environmental management information systems, also play a positive role in this process. The results of the present research can not only enrich the academic literature but also provide a foundation for the widespread implementation of EA. Implementing EA can, in addition to fulfilling the professional responsibilities of the accounting field, act as a deterrent to the reckless behavior of humans toward the environment and contribute to the well-being of living organisms.